THE EFFECTS OF PROCESSING TEMPERATURES ON THE TENSILE PROPERTIES OF RECYCLEDPOLYETHYLENE TEREPHTHALATE (PET)FILAMENTS - Millando Razak, Dio
Plastic waste has various negative impacts on the environment. Polyethylene terephthalate (PET) is one of the most widely used types of plastic. In 2020, one of the mineral water producers in Indonesia will be producing disposable 15-liter gallons using PET material. The production of disposable gallons has the potential to increase the amount of PET plastic waste produced. One good method of handling plastic waste is by recycling it. In this research, gallons of PET waste were recycled to become textile filaments. The resulting filament is then tested for its tensile properties. The parameters used are temperature variations, namely 200, 210, 220, 230, and 240 °C. According to FTIR and XRD analysis, degradation increased with increasing processing temperature and degree of crystallinity, with an optimal extrusion temperature of 210 °C. The highest tensile strength is produced on the filament with an extrusion temperature of 210 °C, which is 64 MPa. The greatest value of elongation at break was obtained for the filament with an extrusion temperature of 200 °C, which was 153%.